Perbandingan Jarak Euclidean dan Manhattan pada Pemetaan Potensial Tanaman Padi Menggunakan K-Means - Khoirul Rizky Asrofi; Risqi Darma Rusdyan; Vion Age Tricahyo (Journal of Information System Research (JOSH), 2025)
This research aims to analyze the potential of rice production in East Java by using 2 methods, namely Euclidean Distance and Manhattan Distance. By applying these two methods, the Department of Agriculture can gain a deeper understanding of the potential of rice production in each district or city. The analysis results show that K-Means with Euclidean Distance and Manhattan Distance can be used to identify areas with low, medium, and high rice potential. Comparison between the two methods using Silhouette Coefficient shows that Euclidean Distance has a superior value of 0.61, compared to Manhattan Distance which reaches 0.58. The findings provide practical solutions for the Department of Agriculture in an effort to improve food security and rice production in East Java, as well as making an academic contribution in the field of agricultural data analysis